Answer:
<em>x = -3 and y = 0</em>
Step-by-step explanation:
<em>It would be more direct to apply elimination in this problem, rather than substitution:</em>
2x + 6y = -6 ⇒ 2x + 6y = -6 ⇒ 10x = - 30
+ 2(4x - 3y = -12) + 8x - 6y = -24
<em>Now let us solve for x through simply algebra:</em>
10x = -30,
<em>x = -3</em>
<em>Substitute this value of x into the first equation to get the value of y:</em>
2( -3 ) + 6y = -6,
-6 + 6y = -6,
6y = 0,
<em>y = 0</em>
The square root of 25/9 is 5/3
Answer:
14.52
Step-by-step explanation:
13.57 + 13.57 x 7% = 13.57 x (1+7/100) =13.57 x 107/100 = 14.52
This is a free app.... why would we pay you to help
36=2*2*3*3=2²*3²
60=2*2*3*5=2²*3*5
LCM(36,60)=2*2*3*3*5=2²*3²*5=180